Case Report: Isolated surgical decompression for compressive internal jugular vein stenosis: case series and literature review - Ma, Haiyang; Zhao, Rui; Lu, Shuaibin; Peng, Weicheng; Peng, Xupeng; Xu, Sheng; Mao, Beibei; Zhu, Guangtong; Hu, Zhiqiang (Frontiers in Surgery, 2025)
BackgroundInternal jugular vein stenosis (IJVS) is an underrecognized cause of cerebral venous outflow obstruction, commonly presenting with nonspecific symptoms such as head-noise, tinnitus, dizziness, headaches, and visual or auditory disturbances. Extrinsic compression by bony structures, particularly transverse process of the atlas (C1), has emerged as a significant but frequently ignored etiology. This study presents the first case series demonstrating that isolated resection of the C1 transverse process can restore venous outflow and provide durable relief of head-noise–dominant symptoms.ObjectiveThis study presents three cases of symptomatic IJVS caused by bony compression, marked by head noise–dominant presentation and failure of conservative or endovascular treatments, emphasizing the diagnostic challenges, individualized surgical strategies, and clinical outcomes, along with a review of current literature.MethodsThree patients with imaging-confirmed compressive IJVS underwent Doppler ultrasound, 3D computed tomography venography, and magnetic resonance imaging. All patients receivedtargeted surgical decompression via resection of the compressive bony structures, with one patient receiving adjunctive venous stenting due to persistent flow limitation.ResultsAll patients achieved significant postoperative improvement, including resolution of head noise and amelioration of associated symptoms. Imaging confirmed improved venous caliber and outflow. Notably, one patient with previous stenting failure benefited from staged decompression and re-intervention, highlighting the value of individualized management.ConclusionExtrinsic compression is a treatable cause of IJVS. Isolated surgical decompression offers a viable treatment option, particularly in patients unresponsive to endovascular approaches. These cases support the need for greater awareness of compressive IJVS and further studies to refine treatment indications and evaluate long-term outcomes.